The Revenue Administration–Gap Analysis Program An Analytical Framework for Excise Duty Gap Estimation - Thackray, Mick (Washington, D.C. International Monetary Fund, 2017)
The IMF Fiscal Affairs Department’s Revenue Administration Gap Analysis Program (RA-GAP) assists revenue administrations from IMF member countries in monitoring taxpayer compliance through tax gap analysis. The RA-GAP analytical framework for estimating excise gaps presented in this Technical Note sets out the steps and data required for comprehensive top-down gap estimates based on a comparison of actual collections to potential collections, which is estimated from consumption (or use) and expenditure of excise commodities. The note outlines the motivation for, and different approaches to, excise gap estimation; and identifies the design criteria for robust gap estimates. The note was jointly produced by RA-GAP team and the Slovak Republic’s Institute for Financial Policy, piloting the framework for the mineral oils excise gap in Slovakia
Keywords: Slovak Republic; Wealth; Revenue administration; Economics; Tax Evasion and Avoidance; Optimal Taxation; Public finance & taxation; Taxes; Saving; Tax gap; National accounts; Excises; National Government Expenditures and Related Policies: General; Expenditure; Revenue performance assessment; Excise taxes; Business Taxes and Subsidies; Taxation, Subsidies, and Revenue: General; Efficiency; Expenditures, Public; Consumption; Macroeconomics; Tax administration and procedure; Macroeconomics: Consumption; Excise tax; Taxation; Public Finance; Fiscal Policies and Behavior of Economic Agents: General; Tax administration core functions